Relationship between trunkal stability and performance measures in tactical athletes - Gleadhill, C.; Stierli, M. (Journal of Australian Strength and Conditioning, 2017)
Policing is a demanding occupation, in which physical tasks such as leaping, jumping and running are performed regularly are improved performance in these tasks is necessary (1). The FMS has gained much traction within the tactical strength and conditioning profession. It is not clear, however, exactly what components of the FMS impact on performance measures specific to operational employment. Previous authors have demonstrated associations of lower body FMS elements and jumping performance (2). Core stability measures, however, have been previously shown to be poor predictors or performance (3). The purpose of this study was to investigate the link between different elements of the Functional Movement Screen (FMS) and a validated test of performance, the triple hop. The null hypothesis of this study was that no elements of the FMS would have any correlation with triple hop performance measures.